Clinical psychology : - Freeman, Arthur (John Wiley & Sons, Inc., 2008)
Clinical Psychology: Integrating Science and Practice paints a vivid portrait of the work of the clinical psychologist and uniquely illustrates clinical psychology's richness and historical significance, as well as its leadership in the scientific development of methods and techniques for clinical assessment and intervention.